Assembly of Cu–In–Sn–Se quantum dot–sensitized TiO2 films for efficient quantum dot–sensitized solar cell application. (September 2021) - Liu, S.; Fan, R.; Zhao, Y.; Yu, M.; Fu, Y.; Li, L.; Li, Q.; Liang, B.; Zhang, W.
Abstract: Ternary I-III-VI (such as CuInSe2 and AgInS2 ) quantum dots (QDs) have been increasingly studied in the field of photoelectric conversion applications. Here, we prepare a relatively less toxic Cu–In–Sn–Se (CISSe) QD by an organic high-temperature hot injection method, and this material is subsequently applied as a functional sensitizer to produce QD-sensitized solar cells (QDSSCs). Because of the effect of Sn doping and ZnS passivation, the TiO2 /CISSe/ZnS photoanode obtains the greatest composite resistance (985.5 Ω·cm 2 ) and highest electron lifetime (120.23 ms) among the experimentally compared materials, showing the further inhibition of charge recombination when compared with bare Cu–In–Se solar cells while effectively enhancing the collection efficiency of photogenerated electrons. Using CISSe/ZnS QDs as a sensitizer, the power conversion efficiency of the QDSSC reaches 6.7%, of which Voc, Jsc, and FF reach 0.559 V, 22.93 mA/cm 2, and 0.52, respectively. It provides a new possibility for the development of QDSSCs. Graphical abstract: A highly efficient and low toxic Cu–In–Sn–Se quaternary quantum dots (QDs) is synthesized by an organic high-temperature hot injection method, functionally applied as a sensitizer for QD-sensitized solar cells (QDSSCs). With the optimization function of Cu–In–Sn–Se QD sensitizer for light absorption rate and light response range, further modified by the suppression effect for charge recombination of ZnS passivation layer, the power conversion efficiency (PCE) of QDSSCs attains 6.7%, much higher than the 5.64% PCE of the pure Cu–In–Se QD-based QDSSCs. Image 1 Highlights: The organic high-temperature hot injection method is used to synthesize quaternary alloy quantum dots of Cu–In–Sn–Se. The Sn element doping and ZnS passivation jointly promote the optical adsorption properties of the photoanode. The QDSSCs based on Cu–In–Sn–Se sensitizer and ZnS passivation layer synergistically achieves an overall PCE of 6.70%.